Research Trends on Immigrant Teachers: A Bibliometric Study - Ferrada-Quezada, N (Richtmann Publishing Ltd, 2025)
This study aims to explore the bibliometric characteristics of research on teacher immigration without a specific time frame. Indexed documents were retrieved from the Scopus database, and then analyzed using the VOSviewer software. The search yielded 438 articles representing 55 countries and 160 journals. Since 2017, the number of articles about this topic has increased. The United States, Canada and China were the three countries with the highest production in this field. Most articles were published in education and cultural studies journals. The institutions with the most active participation in publications from this field were from South-Africa and Canada. The most prolific author is Sadhana Manik; however, no avid producers of research were observed, and citation and collaboration among researchers is scarce. References to Latin-American countries were not found despite the increase in their migrant population in recent years. Therefore, the results call researchers to conduct local and collaborative research in order to deepen the knowledge about this minority, and develop public policies suitable for increasingly diverse populations. Addressing these research gaps and fostering international collaboration is essential to achieving a more complete understanding of teacher migration and its implications for education systems around the world. © 2025 Natalia Ferrada Quezada and Cherie Flores-Fernández.